Immunopsychiatry : an introduction - 4 0 16; (Neil Andrew), Harrison, Neil;Khandaker, Golam M.,;Bullmore, Edward T.,;Dantzer, Robert; 5 (Cambridge : Cambridge University Press, 2021)
The rapidly growing field of immunopsychiatry combines expertise and insights from immunology, psychiatry and neuroscience to understand the role of inflammation and other immune processes in causing and treating mental illness. This represents a major shift in mental health science, traditionally focused on psychological and neuronal mechanisms of depression, psychosis and dementia. This book provides the first comprehensive overview of recent, inter-disciplinary research linking disordered function of the immune system to the brain and mental illness. It offers a broad and deep perspective on the implications of immune system involvement in psychiatric disorders, including a balanced focus on basic science and clinical applications. Chapters cover the scientific evidence linking immune processes to major mental illnesses such as schizophrenia, depression, anxiety and dementia. An invaluable guide for graduate students, doctors in training, scientific researchers and others interested in the link between the immune system and mental health.
Basic concepts in immunobiology / Lorinda Turner and Neil Harrison -- The evolution of immunological research in psychiatric disorders / Prof Keith Kelley -- Stress, immune system and the brain / Julie-Myrtille Bourgognon, Alison McColl, Maria Suessmilch, Rajeev Krishnadas and Jonathan Cavanagh -- Role of infection and inflammatory cytokines / Prof Alan Brown, Fiona Conway, Genvieive Falabella and Carly Apar -- Role of auto-immunity, anti-NMDA receptor and related antibodies / Mike Zandi and Esha Abrol -- Effectiveness of Immunotherapies for Psychotic Disorders / Rachel Upthegrove and Bill Deakin -- Inflammation, sickness behaviour and depression / Neil Harrison, Alessandro Colasanti and Golam Khandaker -- Inflammation, antidepressant response and immunotherapies for depression / Golam Khandaker, Prof Ed Bullmore and Nils Kappelmann -- Role of Microglia in Neurodegenerative Disease / Colm Cunningham and Donal Skelly -- Role of inflammation in Parkinson's disease dementia and dementia with Lewy body / John O'Brien and Ajenthan Surendranathan -- The role of adaptive and innate immunity in Alzheimer's disease / Clive Holmes -- The immune system and anxiety disorders / Vasaliki Michopoulos and Tanja Jovanovic -- Microbiome-gut-brain interactions in autism and other neurodevelopmental disorders / John Cryan, Ted Dinan, Kiran Sandhu and Eoin Sherwin -- Role of the adaptive immune system in resolution of inflammation-associated disorders / Prof Robert Dantzer -- Trans-diagnostic effect of immune system on psychiatric disorders / Prof Bernhard T. Baune.
Title from publisher's bibliographic system (viewed on 03 Sep 2021)
Keywords: 2 -- 0; 6; Psychology, Pathological. -- 20; 20; Electronic books. -- 2